Application and Development of Automatic Speech Recognition in Vehicle Field - LIU Yue; LIN Jun; YOU Jun (Kongzhi Yu Xinxi Jishu)
As a key technology of artificial intelligence, speech recognition has enjoyed widespread popularity, and the appearance of deep learning makes it possible to commercialize speech recognition. This paper gave a detailed description of speech recognition principle and structure, introduced the development of speech recognition based deep learning in history, and then listed critical breakthroughs on acoustic model and language model. Aiming at the application of speech recognition technology, it introduced its application process and the future trends of passenger car. In the meantime, under the requirement of rail transit, it finally described some on-going works carried out and presented some future research trends.